2000
DOI: 10.1097/00008877-200002000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal spermidine administration improves inhibitory avoidance performance in rats

Abstract: Polyamines are polycations present at high concentrations in the mammalian brain. We investigated the effect of an intrahippocampal infusion of spermidine, a polyamine agonist, immediately post-training on the inhibitory avoidance learning paradigm in rats. Bilateral intrahippocampal microinjection of spermidine (0.02-20 nmol) caused an increase in test step-down latencies at low concentrations. Administration of arcaine (0.002-0.2 nmol), an antagonist of the N-methyl-D-aspartate (NMDA) receptor polyamine bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…Polyamines have also biphasic effects on learning and memory, since they facilitate the acquisition and/or early consolidation of inhibitory avoidance (Berlese et al 2005;Guerra et al 2006;Rubin et al 2000Rubin et al , 2001, fear conditioning (Camera et al 2007;Rubin et al 2004) and the 14-unit Tmaze (Shimada et al 1994) tasks at low doses, but have no effect at high doses. Interestingly, spermidine has no effect on late consolidation and retrieval (Berlese et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamines have also biphasic effects on learning and memory, since they facilitate the acquisition and/or early consolidation of inhibitory avoidance (Berlese et al 2005;Guerra et al 2006;Rubin et al 2000Rubin et al , 2001, fear conditioning (Camera et al 2007;Rubin et al 2004) and the 14-unit Tmaze (Shimada et al 1994) tasks at low doses, but have no effect at high doses. Interestingly, spermidine has no effect on late consolidation and retrieval (Berlese et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the facilitatory effects of spermidine on memory are blocked by minute amounts of arcaine, an antagonist of polyamine binding site at the NMDA receptor (Reynolds 1990), the involvement of this receptor in the memory improvement induced by spermidine (Rubin et al 2000(Rubin et al , 2001(Rubin et al , 2004 has been suggested. In line with this view, the noncompetitive NMDAr antagonist, MK-801, reverses the facilitatory effect of spermidine on the memory of fear (Camera et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The post-training intrahippocampal or intra-amygdala administration of low doses of spermidine (0.02-20 nmol) improves inhibitory avoidance performance of rats (Rubin et al, 2000(Rubin et al, , 2001 and attenuates retrieval deficits induced by glutamatergic and cholinergic antagonists in maze tasks (Kishi et al, 1998a,b). As expected, polyamine antagonists impair passive avoidance behavior and prevent the facilitatory effects of spermidine on memory (Rubin et al, 2000(Rubin et al, , 2001. Therefore, it seems that the conflicting effects of polyamines, mainly spermidine, on learning and memory are attributable to the use of a wide range of doses of this compound.…”
Section: Introductionmentioning
confidence: 99%
“…77,78 Among them, especially remarkable is the dual modulation of aamino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) 79 and N-methyl-D-aspartate (NMDA) receptors 80 , which have been implicated in important plasticity events, such as learning and memory. [81][82][83][84][85][86][87] Polyamines (125-250 nmol, i.c.v.) cause damage of hippocampus and learning impairment in rats at high doses 88 and also increases dizocilpineinduced impairment of a learning task in rats.…”
mentioning
confidence: 99%
“…[81][82][83][84][85][86][87] Polyamines (125-250 nmol, i.c.v.) cause damage of hippocampus and learning impairment in rats at high doses 88 and also increases dizocilpineinduced impairment of a learning task in rats. 87 These studies show that high cerebral levels of polyamines are neurotoxic and impair learning and memory.…”
mentioning
confidence: 99%